2011
DOI: 10.1074/jbc.m110.199273
|View full text |Cite
|
Sign up to set email alerts
|

MTA1 Coregulation of Transglutaminase 2 Expression and Function during Inflammatory Response

Abstract: Although both metastatic tumor antigen 1 (MTA1), a master chromatin modifier, and transglutaminase 2 (TG2), a multifunctional enzyme, are known to be activated during inflammation, it remains unknown whether these molecules regulate inflammatory response in a coordinated manner. Here we investigated the role of MTA1 in the regulation of TG2 expression in bacterial lipopolysaccharide (LPS)-stimulated mammalian cells. While studying the impact of MTA1 status on global gene expression, we unexpectedly discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…MTA1 plays an essential role in DNA damage response [35][36][37][38], a process that is important for both normal and cancer cells. Recent advances have also revealed that MTA1 plays a critical homeostatic role in inflammatory responses, both as a target and as a component of the NF-κB circuitry [39][40][41], which links normal and cancer cells. The association of MTA1 with microtubules [19] may endow MTA1 with basic physiological roles in the regulation of cell shape, cell motility, and cell cycle, among other factors.…”
Section: Mta1 Subcellular Localization and Related Functionsmentioning
confidence: 98%
See 1 more Smart Citation
“…MTA1 plays an essential role in DNA damage response [35][36][37][38], a process that is important for both normal and cancer cells. Recent advances have also revealed that MTA1 plays a critical homeostatic role in inflammatory responses, both as a target and as a component of the NF-κB circuitry [39][40][41], which links normal and cancer cells. The association of MTA1 with microtubules [19] may endow MTA1 with basic physiological roles in the regulation of cell shape, cell motility, and cell cycle, among other factors.…”
Section: Mta1 Subcellular Localization and Related Functionsmentioning
confidence: 98%
“…However, the static and co-repressive complex cannot explain the co-activator function of MTA1. MTA1 has been reported to co-activate the transcription of many genes, such as BCAS3 [96], Pax5 [72], MyD88 [40], p19ARF [97], transglutaminase 2 (TG2) [41], HMMR [98], tyrosine hydroxylase (TH) [99], SUMO2 [100], and STAT3 [101]. All of these activities involve MTA1-RNA pol II co-activator complex recruitment.…”
Section: Co-activator Function Of Nuclear Mta1 Involves Nurf and Rna mentioning
confidence: 98%
“…As a part of the NuRD complex, MTA1 regulates transcription of its targets by modifying the acetylation status of the target chromatin and cofactor accessibility to the target DNA [2]. Current models suggest that MTA1 regulates metastatic potential as part of the multiprotein Mi-2/nucleosome remodeling and NuRD by controlling the epithelial-tomesenchymal transition [3,4].…”
Section: Introductionmentioning
confidence: 97%
“…Unexpectedly, MTA1 manifests its dual coregulatory activity in the inflammatory response: under basal condition, MTA1 represses the expression of target cytokine genes while acting as an coactivator of cytokines in LPS-stimulated macrophages [41]. Additionally, LPS stimulation of macrophage is accompanied by increased expression of cytokines [42]; MTA1 also stimulates the expression of transglutaminase 2 - a crosslinking enzyme involved in immediate defense during injury or infection in LPS-stimulated cells [43]. These observations raise an interesting possibility that MTA1 expression is likely to be induced by extracellular signals which themselves induce NF-κB signaling pathway.…”
Section: Mta Proteins In Mammalsmentioning
confidence: 99%